The Representation of Arab immigrants’ identity as portrayed in Diana Abu-Jaber’s novel Arabian Jazz: Postcolonial migrant Theory. - Purwanto, Bambang; Faruk; Munjid, Achmad (Universitas Negeri Semarang, 2025)
The United States has been a successful land of immigration since the late 1800s. The Arab immigration is a part of that fortunate history. This paper aims to represent Arab immigrants' identity through Diana Abu-Jaber’s Arabian Jazz (1993) by using the Postcolonial migrant. The story is about the Ramoud family, who have migrated from Jordan to the United States, and one of them confused identity. Jemorah, Matussem Ramoud's daughter, has “a double-consciousness” where physically she is like an Arab but not her cultural and attitude. She struggled with her identity because she was born in Jordan and grew up as a teenager in Euclid, the United States. Her aunties also insist that Jemorah get married to an Arabian because they want to preserve the heritage, Arab culture, and the family’s honor. Her condition is quite different from Melvina, Jemorah’s younger sister, in that she can adapt well to American culture. This novel also examines identity as a component of hybridity, especially in Jemorah and Melvina, as the main characters. This paper concludes that the second generation of Arab-Americans lost their identity, and it is quite different from the first generation, who preserve their Arab heritage, norms, tradition, values, and identity.